Analisis Pelaksanaan Digitalisasi Arsip Penataan Nagari/Desa sebagai Upaya Peningkatan Efektivitas Administrasi Pemerintahan Provinsi Sumatera Barat - Abdul Hamid Gusri; Rizki Syafril (AHKAM, 2026)
Although the digitalization of government archives has become an important need in supporting the effectiveness of public administration, the management of nagari/village structuring documents that have administrative and legal value still requires a more organized and easily accessible digital archive system. This study aims to analyze the implementation of digital archive digitalization for nagari/village structuring as an effort to improve the effectiveness of government administration at the Bureau of Government and Regional Autonomy of West Sumatra Province. This study used a descriptive qualitative approach with a case study design. The research data sources included archive management activities, administrative documents, and officials directly involved in the archive digitalization process. Data were collected through direct observation, documentation, and involvement in administrative activities from January to March 2026, and were then analyzed through the stages of data reduction, data display, and conclusion drawing. The results showed that archive digitalization was carried out through the stages of document collection, archive classification, scanning, data input, digital storage, and the creation of document access links. Archive digitalization facilitated document retrieval, accelerated the process of territorial administrative verification, improved employee work efficiency, and reduced the risk of losing physical archives. These findings contribute to the development of studies on archive management and public administration based on the Electronic-Based Government System (SPBE). The implications of this study emphasize the importance of improving employee competence, standardizing digital archive management, and providing adequate information technology facilities to support the effectiveness of government administration on an ongoing basis.